Principles of animal research for graduate and undergraduate students - Suckow, Mark A.; Stewart, Kay L. (Academic Press is an imprint of Elsevier, 2017)
"Principles of Animal Research is the first publication to offer a broad look at animal research science for a student, early researcher, or technician. Offering guidance for all aspects of the research experience, including the research and development of a thesis, model selection, experimental design, IACUC protocol preparation, and animal husbandry and technical procedural needs, the book is a necessary addition to every student, technician, and researcher's education"--Publisher's description